Effect of recrystallization and texture on mechanical properties of extruded AA7003 alloy. Issue 7 (11th July 2019) - Du, X.; You, J.; Qu, Y.; Wang, S.; Zhou, N.
Abstract: The microstructure, texture and mechanical properties of AA7003 extrusion sheets processed with different parameters were investigated. Furthermore, the effects of the microstructure and texture on the mechanical properties were discussed. The grain morphology and the texture were analyzed by using a combination of scanning electron microscopy and electron backscatter diffraction. Moreover, the mechanical properties were measured by tensile tests and the tensile fracture morphology was also analyzed by scanning electron microscopy. The results showed that the maximum recrystallization extent occurred at the extrusion process conditions of T = 450 °C and v = 1 mm/s, and the increase in recrystallization extent had a negative effect on the tensile strength. Moreover, a relatively strong recrystallization cube orientation <100> existed when the extrusion temperature was 470 °C, showing a high tensile strength and elongation. Thus, it can be concluded that the cube texture is beneficial to the tensile strength and elongation in extruded AA7003 alloy.